Cognitively Inspired Cyber Physical Systems Design through Brain Signal Analysis and Decoding - Gupta, Richa (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Cybernetics, or the study of control and communication, informs the design, modelling, and characterization of cyber-physical systems. In order to construct functional cyber-physical systems in the actual world, the thesis presents a unique method for analysing and decoding brain signals involved in cognitive processes. The goal of this research is to create and evaluate next-generation cyber-physical systems that, when connected to a human brain via a brain-computer (BCI) interface, can read the human brain's neural code and act as smart tools in fields like medicine, gaming, affective computing, and the study of subjective creativity. The non-invasive examination of human memory for the potential early prediction of memory-related disorders like dementia and prosopagnosia is one example of the healthcare application. The use of brain-computer interfaces to simulate the skills of human game trainers for the purpose of robotic game instruction is also discussed. Due to a lack of qualified individuals and the inherent monotony of the work, it is essential that human game trainers be replaced by robots. Using the predicted brain-connectivity (anticipated signalling routes) between active brain lobes/regions, affective computing apps attempt to identify human emotional states. A network study of human emotions has potential for use in psychotherapy. The implementation of a creativity test is crucial for solving issues related to scientific creativity by autonomously detecting subjective creativity from the brain's reaction to memory-generated stimuli.